Implementasi Doktrin Responsibility to Protect (Humanitarian Intervention) dalam Hukum Internasional (Kasus Kosovo Libya dan Suriah) (Lex Jurnalica, 2012)
AbstractThe principle of State sovereignty is no longer traditionally understood, as the absolute power of the state to regulate its internal affairs, but also the state's obligation to provide protection for its residents. Along with this principle and the development of the international law, the doctrine of responsibility to protect (the obligation to protect) has been introduced by jurist of international law. The main idea of this doctrine is that International community has an obligation to protect the civilians of any nationality if a state is not capable of providing protection to the population or even become perpetrators of violence against the population. This paper will review how the arrangement of this doctrine in international law and to what extent this doctrine might be implemented  are essential elements    to be elaborated in this article with reference to the case of intervention (military) NATO in Yugoslavia in 1999, in Lybia in 2011 and the potential for intervention (military) in SyriaKeywords: sovereignity,  responsibilty to protect, military intervention AbstrakPrinsip Kedaulatan Negara dalam perkembangannya tidak lagi dipahami secara tradisional, yaitu kekuasaan mutlak negara untuk mengatur urusan dalam negerinya, namun juga kewajiban negara memberikan perlindungan bagi penduduknya. Bersamaan dengan itu pula muncul doktrin responsibility to protect (kewajiban untuk melindungi). Komunitas Internasional memiliki kewajiban untuk melidungi warga sipil kewarganegaraan manapun apabila suatu negara dianggap tidak mampu memberikan perlindungan terhadap penduduknya atau bahkan menjadi pelaku kekerasan terhadap penduduknya tersebut. Paper ini akan mengulas bagaimana pengaturan doktrin ini dalam hukum Internasional  dan sejauhmana doktrin ini dapat diterapkan menjadi kajian yang menarik untuk dibahas dengan mengacu kepada Kasus intervensi (militer) NATO di Yugoslavia tahun 1999, di Lybia tahun 2011 dan potensi intervensi (militer)  di Suriah.Kata kunci: kedaulatan, tanggung jawab melindungi, intervensi militer